Practice patterns on the management of secondary hyperparathyroidism in the United States: Results from a modified Delphi panel - David E. Henner; Beatrice Drambarean; Teresa M. Gerbeling; Jessica B. Kendrick; William T. Kendrick; Lisa Koester-Wiedemann; Thomas L. Nickolas; Anjay Rastogi; Anis A. Rauf; Brenda Dyson; Michael C. Singer; Pooja Desai; et al. (PLoS ONE, 2025)
Background Secondary hyperparathyroidism (SHPT) is common in patients with chronic kidney disease (CKD). Many recommendations in the Kidney Disease Improving Global Outcomes (KDIGO) CKD-mineral and bone disorder guidelines are supported by modest evidence and predate the approval of newer agents. Therefore, an expert panel defined consensus SHPT practice patterns in the United States with real-world context from the nephrology community. Methods Ten US healthcare providers and one patient participated in a modified Delphi method comprising three phases. Consensus was determined via iterative responses to a questionnaire based on the 2009 and 2017 KDIGO guidelines and published literature on the identification, evaluation, monitoring, and interventional strategies for patients with SHPT. The threshold for consensus was 66% agreement. Results Panelists generally agreed with KDIGO recommendations, with some differences. Consensus was reached on 42/105 (40%), 95/105 (90.5%), and 105/105 (100%) questions after phases 1, 2, and 3, respectively. Panelists unanimously agreed that SHPT treatment is often started late. There was a preference for serum phosphate level <4.6 mg/dL, and consensus to maintain serum calcium levels <9.5 mg/dL. There was unanimous agreement for vitamin D analogues as first-line options in patients not on dialysis with severe, progressive SHPT and unanimous preference for intravenous calcimimetic, etelcalcetide, in appropriate in-center dialysis patients. Factors such as formularies, dialysis center protocols, and insurance were recognized to influence therapeutic strategies. Conclusions Expert consensus was reached on SHPT management, further defining therapeutic strategies and medication use and emphasizing need for treatment early. Despite evidence-based treatment preferences supported by clinical experience, factors other than scientific evidence influence decision making, particularly with medications.